Mathematic Learning Management on One Day School at SMP Islam Plus Assalamah Ungaran - Pujiastuti, Pujiastuti (2012)
Mathematic aims to develop the ability to calculate, measure, formulate, and use mathematical formula that is needed in daily life. With mathematic learning on one day school, students are able to understand the material and the learning goals can be achieve well. This study has three objectives. The first is to describe the characteristics of teaching activity in Mathematic learning on one day school at SMP Islam Plus Assalamah Ungaran. The second is to elaborate the characteristics of instructional activity in Mathematic learning on one day school at SMP Islam Plus Assalamah Ungaran. And finally, this study aims to describe the characteristics of interaction in Mathematic learning on one day school at SMP Islam Plus Assalamah Ungaran. It is a qualitative research using ethnography design. This study was done at SMP Islam Plus Assalamah Ungaran. The informant of this research paper consists of the principal, teacher and student. The method of collecting data uses in-depth interview, observation, and documentation. Data analysis used is an analysis arranged in site. Data validity in this paper uses triangulation. The findings show that: (1) Teacher's activity of teaching includes implementing of the student-centered learning by developing the ability to think critically and creatively and be able to solve problems and create a classroom as an attractive learning environment. The teacher directs learning on an independent learning and improves student's participation by providing exercises, using varied teaching methods, and providing individual guidance. Teacher uses media such as visual aids, LCD, and the environment to facilitate students' understanding of the subject matter. (2) Student's activity of learning includes visual activity, listening activity, drawing activity, mental activity, and emotional activity through several instructional activities which are determined by the teacher. The activity of learning is directed to improve student's participation in learning by using the varied instructional methods. The student's activity of learning is directed to improve students' skill and creativity in learning through the activity of making a product. It is also directed to improve student's ability in analyzing and understanding the instructional material through the observation and improve student's ability in analyzing problems by giving exercises to be done. (3) The interaction that exists in learning consists of the one-way interaction, two-ways interaction and multidirectional. The instructional interaction is to develop the academic ability and social skill including interpersonal skill, train the cooperation between the team members in achieving the goal, and develop the individual ability.